Influence of Enzootic Bovine Leukosis on phagocytic function of circulating leukocytes from animals with persistent lymphocytosis - Azedo, Milton Ricardo (2008)
This study evaluated the phagocytosis of propidium iodide-labeled Staphylococcus aureus (PI-Sa) by circulating leukocytes obtained from five Enzootic Bovine Leukosis (EBL)-negative cows, five naturally EBL-infected, non-lymphocytotic cows, and five EBL-positive cows with persistent lymphocytosis (PL), analyzed by flow cytometry. Among cells obtained from EBL-infected cows, presenting PL, the percentage of leukocytes carrying out phagocytosis (7.20%), was smaller (p=0.047) than that verified among cells obtained from non-infected (12.90%), and from BLV-infected, non-lymphocytotic cows (14.70%). Furthermore, leukocytes obtained from EBL-infected cows, presenting PL, showed smaller phagocytosis intensity (characterized by the intensity of propidium iodide fluorescence) than leukocytes obtained from non-infected and from EBL-infected, non-lymphocytotic, cows (p<0.001). Therefore, results show a decreased phagocytic function among circulating leukocytes obtained from BLV-infected, lymphocytotic cows.